Pembentukan Karakter Anak melalui Permainan Tradisional di Kampoeng Dolanan Surabaya - Rofifah, Alfinaa Mufidatur; Roesminingsih, Maria Veronica (J+PLUS UNESA, 2023)
The issue in this study is the process of character formation in children through traditional games, specifically how standard games may keep the character values included in them in order to mold the character of each unique kid. This study employs a qualitative technique with descriptive analytical writing. In-depth interviews, interactive observation, and documentation were used to obtain data for this study. The chairman of Kampoeng Dolanan Surabaya, volunteers from Kampoeng Dolanan Surabaya, children, and parents were the subjects of this study. The findings revealed that traditional games, as well as different strategies for communicating traditional games, can assist form character in youngsters both during and after play. There are just five sorts of games available Traditional games in Kampoeng Dolanan are thought to embody strong character characteristics like as responsibility, loyalty to rules, teamwork, and honesty, based on the vast number of aficionados for these activities. Of the four types of character values found in the five traditional games included for this study. These character characteristics can be established in each unique kid while or after playing by needing time that is not only played once but also demands the youngster to play multiple times.